PepH3-modified nanocarriers for delivery of therapeutics across the blood-brain barrier - Anikó Szecskó; Mária Mészáros; Beatriz Simões; Marco Cavaco; Catarina Chaparro; Gergő Porkoláb; Miguel A.R.B. Castanho; Mária A. Deli; Vera Neves; Szilvia Veszelka (Fluids and Barriers of the CNS)
Abstract Background Nanocarriers targeting the blood-brain barrier (BBB) are promising drug delivery systems to enhance the penetration of therapeutic molecules into the brain. Immunotherapy, particularly monoclonal antibodies designed to bind amyloid-beta peptides have become a promising strategy for Alzheimer’s disease, but ensuring efficacy and safety is challenging and crucial for these therapies. Our aim was to develop an innovative nanocarriers conjugated with PepH3, a cationic peptide derived from Dengue virus type-2 capsid protein that crosses the BBB and acts as a shuttle peptide for the encapsulated single domain antibody (sdAb) recognizing Aβ oligomers. Results PepH3 peptide enhanced the uptake of the nanoparticles (NPs) into brain endothelial cells, and transcytosis of sdAb, as a potential therapeutic molecule, across both rat and human BBB culture models. The cargo uptake was a temperature dependent active process that was reduced by metabolic and endocytosis inhibitors. The cellular uptake of the cationic PepH3-tagged NPs decreased when the negative surface charge of brain endothelial cells became more positive after treatments with a cationic lipid or with neuraminidase by digesting the glycocalyx. The NPs colocalized mostly with endoplasmic reticulum and Golgi apparatus and not with lysosomes, indicating the cargo may avoid cellular degradation. Conclusions Our results support that combination of NPs with a potential brain shuttle peptide such as PepH3 peptide can improve the delivery of antibody fragments across the BBB.